Application of Fe Based Composite Catalyst in Biomass Steam Gasification to Produce Hydrogen Rich Gas - Zhou, Liang; Yang, Zhiyong; Wei, Deju; Zhang, Heng; Lu, Wei (Frontiers in Chemistry, 2022)
A series of composite catalysts with different Fe-based load amounts were prepared and applied to the experiment of biomass gasification assisted by steam. The structure of the catalyst was analyzed by XRD, SEM, TEM, N2 adsorption-desorption, and H2-TPR. The effect of the change of Fe load amounts on the catalytic activity was studied, and the optimal conditions of the gasification reaction were selected. The relationship between catalyst structure and catalytic capacity was clarified. The results showed that under the optimal reaction conditions, the catalyst showed better catalytic activity when Fe load amounts were 10%. The proportion of hydrogen in the gasification gas is as high as 42.2% and the hydrogen production is 27.65 g/kg. The tar content reaches the lowest value of 34.07g/Nm3.